Treatment of cervical cancer - Te Linde, R. (2015)
Before considering particularly the treatment of carcinoma of the neck, it is necessary to briefly refer to methods of diagnosis and classification process in several stages. Our interpretation of the diagnosis and classification has a very important role in our choice of treatment in each individual case influence. As developed cn use of cytology and biopsy, many early cases can be discovered, which had not been recognized ten or more years ago. Some of these are in the preinvasive stage when the disease is still curable 100%.